Effects of socioeconomic characteristics on online purchase intention among Malaysians - Imtiaz Ali, Najma; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Brohi, Imtiaz Ali; Shah, Asadullah (American Scientific Publishers, 2019)
Online shopping has gained high popularity across all groups of society in Malaysia since its commencement and continued to grow every day. Malaysia being the central hub of South-East Asia has been considered as a favourite place for shopaholic people for physical shopping and the same trend is seen in terms of online shopping. While the socioeconomic characteristics of society have been studied to measure various consumer behaviours within different contexts including Malaysia. However, the Malaysians attitude towards online purchase behaviour is one of the significant areas that need to be investigated, hence, this study focuses on measuring the socioeconomic attitude towards online purchase intention. A total of 400 complete questionnaire were collected by using convenience sampling method within shopping malls of Klang Valley region through face to face questionnaires distribution technique. Two inferential statistical tests were used to measure the relationship between various characteristics of socioeconomics group towards the online purchase intention. These tests were independent sample T-test and univariate analysis of variance (ANOVA). A T-test was used to evaluate the effect of gender towards the online purchase intention, whereas one-way ANOVA was performed to check the significant effect of age, monthly income, and education towards the online purchase intention. The results revealed that there is a significant difference based on the age and income; while individuals with higher income shop more as compared to individuals with less income and the individuals within the income group of 5000 to 7000 shop more as compared to other income groups. Whereas, individuals between the age group of 41 to 50 shopped more as compared to other age groups. Furthermore, the results also revealed that there was no significant difference found in terms of gender and education, male and female shopped online despite of their gender and education background.